Avaliação da atividade citotóxica, clastogênica e genotóxica do composto ditionato de cis-tetraamino(oxalato)rutênio(III) em linfócitos do sangue periférico humano - REZENDE, Manuela da Rocha Matos (2010)
Chemotherapy agents are increasingly being utilized due to their promising effects in cancer treatment. The desired actions of these drugs are obtained at the cost of frequent and severe side effects. It is essential that drugs utilized for cancer treatment are tested in relation to not only their cytotoxic, but also their clastogenic and genotoxic potentials to establish their clinical risk. Thus, there is increased interest in searching for new metallic compounds presenting antitumor activity with therapeutic potential and reduced side effects, such as those containing platinum (Pt), iron (Fe), titanium (Ti), rhodium (Rh), gold (Au) and ruthenium (Ru). In this work, the cytotoxic, clastogenic and genotoxic properties of cis-tetraamine(oxalato)ruthenium(III) dithionite, cis-[Ru(C2O4)(NH3)4]2(S2O6), were evaluated in peripheral human blood lymphocytes in vitro. Mitotic index (MI), chromosomal aberrations (CA) and DNA damage were analyzed by comet assay. The MI values of human peripheral blood lymphocyte cultures treated with 0.0075, 0.075, 0.75 and 7.5 μM cis-[Ru(C2O4)(NH3)4]2(S2O6) were 6.1, 3.9, 3.2 and 0.2%, respectively. The lowest concentration 0.0075 did not show cytotoxic activity compared to negative control. The CA values obtained for the 0.0075, 0.075 and 0.75 μM concentrations presenting low frequency (1.5, 1.6 and 2.3%, respectively) not expressing clastogenic activity compared to negative control and only at the highest concentration 7.5 μM, showed clastogenic activity, predominantly chromatid breaks and gaps. The data obtained by the comet assay, using cis-[Ru(C2O4)(NH3)4]2(S2O6), suggest that this compound does not show genotoxic activity at concentrations lower than 0.0075 μM. The results of these studies show that cis-[Ru(C2O4)(NH3)4]2(S2O6) has no potential cytotoxic, clastogenic and genotoxic in vitro at concentrations less than or equal to 0.0075 μM.